2019
DOI: 10.1111/jcmm.14680
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol decreases CD45+CD206 subtype macrophages in LPS‐induced murine acute lung injury by SOCS3 signalling pathway

Abstract: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) are life‐threatening condition in critically ill patients. Resveratrol (Res), a natural polyphenol, has therapeutic effect in animal model with ALI; however, whether Res attenuates ALI through modulation of macrophage phenotypes in the animal model remains unknown. We in this study treated LPS‐induced murine ALI with 30 mg/kg Res and observed significantly reduced severity of ALI in the Res‐treated mice 48 hours after Res treatment. Neutrophil in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Our previous study showed that Siglec F+ subtype macrophages were decreased in the mice with ALI, but that was reversed by administration of anti-oxidant resveratrol, indicating a useful new biomarker of M2 macrophage, that was similar to CD206 (8). Consistent with the previous results, we in this study also observed significantly more population of anti-inflammatory Siglec F+CD206+ M2 subtype macrophages in the aCALR-treated mice with ALI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our previous study showed that Siglec F+ subtype macrophages were decreased in the mice with ALI, but that was reversed by administration of anti-oxidant resveratrol, indicating a useful new biomarker of M2 macrophage, that was similar to CD206 (8). Consistent with the previous results, we in this study also observed significantly more population of anti-inflammatory Siglec F+CD206+ M2 subtype macrophages in the aCALR-treated mice with ALI.…”
Section: Discussionsupporting
confidence: 91%
“…A body of evidences showed that macrophages can be modulated by many reagents (4)(5)(6)(7). Our previous research revealed that antioxidant resveratrol can attenuate ALI through polarization of alternatively activated macrophage or M2 cells (8). The therapeutic effects were associated with STAT3/SOCS3 signaling pathway.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, we believe that macrophages are a particularly interesting population for further study as they are recruited to the implant site 38 and fuse together to form multinucleated giant cells that are in direct contact with the scaffold 46 . Resveratrol has extensively been shown to polarize macrophages to an anti‐inflammatory phenotype 32,58–60 . Interestingly, anti‐inflammatory macrophages use fatty acid oxidation as their key energy source compared to proinflammatory macrophages that use glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It exhibits protective effects in various ALI models. In a LPS-mediated ALI model, resveratrol can counteract lung inflammation by suppressing CD45 + Siglec F − and CD45 + CD206 − M1 subtype macrophages [ 76 ]. In a sepsis-induced ALI model, resveratrol can suppress the production of proinflammatory cytokines and the apoptosis of alveolar macrophages through the activation of the vascular endothelial growth factor-B (VEGF-B) pathway, thereby exhibiting anti-inflammatory and antiapoptotic effects [ 77 ].…”
Section: Potential Effects Of Herbal Active Ingredients On Experimental Alimentioning
confidence: 99%